ANALISIS PENGARUH PROMOSI DAN E-WOM, TERHADAP MINAT BELI PELANGGAN MONARCH DENGAN DIMEDIASI BRAND IMAGE - Hartono, Alexander Hartono; Kodrat, David (PERFORMA, 2023)
This study aims to determine the effect of promotion and Electronic Word of Mouth (E-Wom) on the buying interest of Monarch customers mediated by brand image. This study used a causal quantitative approach using 200 respondents. The analysis technique used is the Structural Equational Model with the support of Smart-Partial Lest Square. The results showed that promotions and E-Wom had a positive effect on buying interest. Then the brand image variable is able to mediate the influence of promotion and E-Wom on buying interest. Keywords: promotion, E-Wom, Buying interest, brand image